An investigation into the factors influencing the health status of the coloured people of the Western Cape in an urban setting - Stellenberg, Ethelwynn L. (Ethelwynn Linda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DCur)--Stellenbosch, 2000.